Promoting the replacement of chemical fertilizer with organic fertilizer: the role of policy incentives and digital technology - Liao, Feng; Zheng, Yangyang; Wang, Xiaofeng (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe replacement of chemical fertilizer with organic fertilizer is an important way to improve agricultural non-point source pollution and achieve green agricultural development. However, the current adoption rate of organic fertilizer among farmers is relatively low, and the economic and environmental benefits of organic fertilizer are difficult to realize.MethodsBased on the assumption of bounded rationality and combining evolutionary game theory, this paper constructs a symmetric game model of farmers under three scenarios: no external intervention, government incentives, and digital technology integration, deeply exploring the strategy choices of farmers and the effectiveness of intervention measures in different scenarios.Results and discussionIncome levels have a differentiated impact on farmers’ learning and imitation behaviors. Government subsidies can significantly increase the willingness to apply organic fertilizer in the short term, but due to the heavy financial burden, it is difficult to sustain in the long run. Policy promotion can strengthen farmers’ moral constraints, but the effect of moral constraints is limited due to the long-term nature of ecological moral cultivation. In the absence of government subsidies, developing digital technology can also promote adopting organic fertilizer. The breakthrough of this paper lies in integrating behavioral insights, incentive policies, and digital technologies to comprehensively analyze the influencing factors of organic fertilizer application, and explore how to encourage farmers to adopt organic fertilizer in the absence of subsidies. This contributes to the formulation and improvement of organic fertilizer subsidy policies, with both theoretical and practical significance for enhancing agricultural competitiveness and achieving the green transformation of agriculture.